Impact of recycled concrete aggregate particle size on the strength of soil mixtures for subgrade improvement - Thi Kim Thoa Ho; Hoang Khanh Le (CTU Journal of Innovation and Sustainable Development)
Subgrade improvement applications have extensively investigated the financial and ecological benefits of utilizing recycled concrete aggregate (RCA) waste. This solution has been widely studied in recent decades. This study presents the findings of the relationship between different sizes of recycled concrete aggregate (RCA) particles and certain properties of SRCA blends by adding cement. The test results showed that adding RCA with cement to unstabilized soil significantly improved its compressive strength behavior. Incorporating RCA into the soil mixture can more than double its compressive strength. Integrating larger RCA particle sizes into unstabilized soil decreased the optimum moisture content (OMC) while increasing the maximum dry density (MDD). Conversely, using finer RCA particle sizes in soil mixtures increased the compressive strength compared to larger RCA particles. This blend of RCA-stabilized expansive soil is suitable for subgrade improvement applications, such as building low-traffic volume roads and ensuring embankment stability.